Harnessing the Capabilities: The Synergistic Potential of Quantum Computing in Addressing Limitations of Artificial Intelligence (Global Journal of Computer Science and Technology, 2024)
With the rapid advancement in technological fields two major domains including Quantum computing and artificial intelligence are substantially transforming the internet world Although AI has fundamentally made rapid progress it still has many limitations that are hindering its full potential to efficiently deal with intricate challenges QC on the other hand is an emerging field that has the potential to efficiently handle and minimize these limitations thereby opening new doors of success for artificial intelligence applications This article explored the capacity of QC in alleviating the limitations of AI and thus unfolding novel opportunities in the world of technology It further explored the advantages of quantum computing over classical computing methods The findings suggested that quantum computing can replace classical computing in various computational tasks Moreover it holds significant potential in addressing complex problems and minimizing the challenges associated with artificial intelligence
Keywords: quantum computing; artificial intelligence; algorithms; quantum neural networks (QNNS); encryption